Risk assessment for primary coronary heart disease event using dynamic bayesian networks - Orphanou, Kalia; Stassopoulou, Athena; Keravnou-Papailiou, Elpida (My University, 2015)
Coronary heart disease (CHD) is the leading cause of mortality worldwide. Primary prevention ofCHDdenotes limiting a firstCHDevent in individuals who have not been formally diagnosed with the disease. This paper demonstrates how the integration of a Dynamic Bayesian network (DBN) and temporal abstractions (TAs) can be used for assessing the risk of a primaryCHDevent. More specifically, we introduce basic TAs into the DBN nodes and apply the extended model to a longitudinal CHDdataset for risk assesment. The obtained results demonstrate the effectiveness of our proposed approach.
Keywords: Dynamic Bayesian networks; Primary coronary heart disease; Risk assessment; Temporal abstraction; Temporal reasoning